2020
DOI: 10.3390/ijms21124452
|View full text |Cite
|
Sign up to set email alerts
|

A Peptidic Thymidylate-Synthase Inhibitor Loaded on Pegylated Liposomes Enhances the Antitumour Effect of Chemotherapy Drugs in Human Ovarian Cancer Cells

Abstract: There is currently no effective long-term treatment for ovarian cancer (OC) resistant to poly-chemotherapy regimens based on platinum drugs. Preclinical and clinical studies have demonstrated a strong association between development of Pt-drug resistance and increased thymidylate synthase (hTS) expression, and the consequent cross-resistance to the hTS inhibitors 5-fluorouracil (5-FU) and raltitrexed (RTX). In the present work, we propose a new tool to combat drug resistance. We propose to treat OC cell lines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Tumor microenvironment immune cells constitute a key factor of tumor tissues with increasing evidence supporting their clinicopathological significance in predicting survival status and therapeutic efficacy of tumor patients [ 14 17 ]. Specifically, the infiltration level of TAM accelerates the progression of ovarian cancer [ 18 , 19 ]. TAM consist primarily of M2 macrophages, likely due to exposure to complex factors in the tumor microenvironment [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor microenvironment immune cells constitute a key factor of tumor tissues with increasing evidence supporting their clinicopathological significance in predicting survival status and therapeutic efficacy of tumor patients [ 14 17 ]. Specifically, the infiltration level of TAM accelerates the progression of ovarian cancer [ 18 , 19 ]. TAM consist primarily of M2 macrophages, likely due to exposure to complex factors in the tumor microenvironment [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown that the proper drug combination sequence of cDDP:LR, RTX:LR, and 5-FU:LR, where LR was wrapped into a specific peptide delivery system or encapsulated into PEGylated pH-sensitive liposomes, was able to counteract resistance to cDDP and anti-hTS drugs. In particular, we observed that the simultaneous treatment or 24 h pretreatment of cells with the peptide followed by either agent produced synergistic effects even in resistant cells …”
Section: Results and Discussionmentioning
confidence: 86%
“…In particular, we observed that the simultaneous treatment or 24 h pretreatment of cells with the peptide followed by either agent produced synergistic effects even in resistant cells. 57 In the present study, FA−LR is combined with concentrations of RTX in the low nanomolar range ( 10…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a number of researchers have proposed liposomal surface modifications as a way to overcome these limitations. Various polymers were successfully applied to improve the surface properties of liposomes, including synthetic polymers (pluronics and polyethylene glycol) [ 8 , 9 , 10 ] and natural polymer (peptide, protein, and polysaccharides) [ 11 , 12 ]. Among them, polysaccharides are the most extensively used polymers for liposome modification owing to non-toxicity, non-immunogenicity, good biocompatibility and biodegradability.…”
Section: Introductionmentioning
confidence: 99%